Associations between ambient air pollution and cancer incidence in Taiwan: an ecological study of geographical variations - Shih-Yung Su; Yung-Po Liaw; Jing-Rong Jhuang; Shu-Yi Hsu; Chun-Ju Chiang; Ya-Wen Yang; Wen-Chung Lee (BMC, 2019)
Abstract Background Air pollution is a global public health concern. The World Health Organization has recently set up a goal of saving 7 million people globally by 2030 from air pollution related death. We conducted an ecological study of geographical variation to explore the association between air pollution (specifically, particulate matter <2.5 μm in aerodynamic diameter [PM2.5], particulate matter <10 μm in aerodynamic diameter, sulfur dioxide, nitrogen dioxide, nitric oxide, and ozone) and cancer incidence in Taiwan, from 2012 to 2016. Methods In this study, the yearly average concentrations of each air pollutant at 75 air quality monitoring stations were calculated, and using the kriging method, the concentrations were extrapolated to each and every geographical central point of 349 local administrative areas of Taiwan. Spearman rank correlation coefficients between the age-adjusted cancer incidence rates and various air pollutants were calculated by stratifying genders and urbanization degrees of the local administrative areas. A total of 70 correlation coefficients were calculated. Results In total, 17 correlation coefficients were significantly positive at an alpha level of 0.05. Among these, four correlation coefficients between the age-adjusted cancer incidence rates and PM2.5 levels remained significant after Bonferroni correction. For men in developing towns, general towns, and aged towns and for women in aged towns, the age-adjusted cancer incidence rates increased 13.1 (95% confidence interval [CI], 8.8-17.6), 11 (95% CI, 5.6-16.4), 16.7 (95% CI, 6.9-26.4), and 11.9 (95% CI, 5.6-18.2) per 100,000 populations, respectively, for every 1 μg/m3 increment in PM2.5 concentrations. Conclusions A significantly positive correlation was observed between the PM2.5 level and cancer incidence rate after multiple testing correction.